The Role of Tax Law in Encouraging National Economic Development to Realize State Goals - S.T. Kansil, Christine; Fadloli, Muhammad (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Taxes are a source of state revenue collected from the public based on legislation and used to finance state interests, including the execution of tasks for the public good. The relationship between taxes and development in Indonesia is very close, as infrastructure development can be realized thanks to tax revenue. The taxes paid by the community are used to finance government expenditures, including public projects such as road widening and asphalting in rural and urban areas. This development aims to ensure that the community has adequate transportation access, so that daily activities run smoothly. Taxes serve as an important source of government funding to finance various activities, including development. Therefore, taxes play a key role in the administration of the state.